2018
DOI: 10.3389/fimmu.2018.01595
|View full text |Cite
|
Sign up to set email alerts
|

Thymic Stromal Lymphopoietin Isoforms, Inflammatory Disorders, and Cancer

Abstract: Thymic stromal lymphopoietin (TSLP) is a pleiotropic cytokine originally isolated from a murine thymic stromal cell line. TSLP exerts its biological effects by binding to a high-affinity heteromeric complex composed of thymic stromal lymphopoietin receptor chain and IL-7Rα. TSLP is primarily expressed by activated lung and intestinal epithelial cells, keratinocytes, and fibroblasts. However, dendritic cells (DCs), mast cells, and presumably other immune cells can also produce TSLP. Different groups of investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
175
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 167 publications
(180 citation statements)
references
References 180 publications
(332 reference statements)
1
175
0
4
Order By: Relevance
“…The high fold change of lfTSLP is likely due to its very low expression levels at steady state, while the short form is expressed constitutively in much higher abundance. Our results further highlight a potentially important functional dichotomy between the two TSLP isoforms …”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The high fold change of lfTSLP is likely due to its very low expression levels at steady state, while the short form is expressed constitutively in much higher abundance. Our results further highlight a potentially important functional dichotomy between the two TSLP isoforms …”
Section: Discussionmentioning
confidence: 56%
“…The rs1837253 T allele (minor allele) is associated with a lower risk of asthma and hence considered to have a “protective” effect on asthma development . The TSLP gene encodes two transcript variants in humans: a long TSLP isoform (lfTSLP) and a short TSLP isoform (sfTSLP) . The C terminal of the long isoform, common to both isoforms, can be used to evaluate total TSLP transcripts.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence indicates that TSLP is also involved in chronic inflammatory (i.e., chronic obstructive pulmonary disease, and celiac disease) and autoimmune (e.g., psoriasis, rheumatoid arthritis) disorders and several cancers. These emerging observations greatly widen the role of TSLP in different human diseases …”
Section: Discussionmentioning
confidence: 99%
“…These emerging observations greatly widen the role of TSLP in different human diseases. 18 The goal of this study was to provide new insights into the relationship between vitiligo and TSLP mRNA expression level which is possibly involved in vitiligo pathogenesis. Our results revealed that there was a statistically significant difference of TSLP mRNA expression levels with lower expression in vitiligo patients than in control subjects (P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Upon activation, mast cells store and release a large repertoire of biologically active mediators that have potential positive or negative effects on various target cells [25, 26]. These cells and their mediators have been canonically associated with a detrimental role in allergic diseases [4, 27].…”
mentioning
confidence: 99%